2014
DOI: 10.1007/s11274-014-1656-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycelial antineoplastic activity of Agaricus blazei

Abstract: Basidiocarp of Agaricus blazei (=Agaricus brasiliensis; =Agaricus subrufescens) is used as teas or capsules due to its antineoplastic effect but there are few reports of using mycelium for this purpose. The objective of this study was to evaluate the antineoplastic activity on sarcoma 180 cells implanted in mice of two forms of preparation of the mycelium from two A. blazei strains grown in culture medium with different concentrations of isolated soy protein. Mycelia were grown in Pontecorvo medium with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
1
19
0
3
Order By: Relevance
“…It suggests that the culture medium formulation can affect mycelial biomass yield, mycelial chemical components and, therefore, enhance antineoplastic activity on S180. However, Bertéli et al (2014) did not find Table 1. He = erythrocyte, Hb = hemoglobin, Ht = hematocrit, Lc = total leukocyte, Nt = neutrophil (segmented), Lf = lymphocyte.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It suggests that the culture medium formulation can affect mycelial biomass yield, mycelial chemical components and, therefore, enhance antineoplastic activity on S180. However, Bertéli et al (2014) did not find Table 1. He = erythrocyte, Hb = hemoglobin, Ht = hematocrit, Lc = total leukocyte, Nt = neutrophil (segmented), Lf = lymphocyte.…”
Section: Discussionmentioning
confidence: 88%
“…Bertéli et al (2014) reported A. blazei mycelia of 19.6 mg/mL when ISP was used as nitrogen source in submerged cultivation. Hamedi et al (2007) verified A. blazei mycelial production utilizing non-protein sources such as ammonium oxalate, potassium nitrate, ammonium sulfate, ammonium chloride and urea with maximum yield of 1 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations